Tendency and Coverage of Newspaper toward Political Parties in the Permatang Pauh by-Election in Malaysia - Mohd Azizuddin Mohd Sani (International Review of Management and Marketing, 2016)
This paper is based on a research about newspapers’ coverage during the Permatang Pauh By-Election which was held on 7 May 2015. Five newspapers were selected are the Utusan Malaysia, Berita Harian, Sinar Harian, New Straits Times and the Star. This research will determine the coverage of the press in term of biasness tendency toward political parties contested in the by-election. The Permatang Pauh by-election was contested by four candidates, consisting of former opposition leader Wan Azizah Wan Ismail from People’s Justice Party (PKR), Barisan Nasional (BN)’s Suhaimi Sabudin, Malaysia’s People’s Party (PRM)’s Azman Shah Othman and independent candidate Salleh Isahak. This by-election was won by Wan Azizah Wan Ismail. However, this research has been able to find the link between ownership with the biasness of print media toward political parties empirically. It also shows the daily coverage of newspapers during the by-election. The finding is that all newspapers were bias toward the ruling BN, except for the Sinar Harian which was balance in its coverage.